Decompensated right heart failure, intensive care and perioperative management in patients with pulmonary hypertension: updated recommendations from the Cologne Consensus Conference 2018 - Olsson, Karen Maria; Halank, Michael; Egenlauf, Benjamin; Fistera, David; Gall, Henning; Kaehler, Christian; Kortmann, Kathrin; Kramm, Thorsten; Lichtblau, Mona; Marra, Alberto M.; Nagel, Christian; Sablotzki, Armin; et al. (International journal of cardiology, 2018)
In June 2016, members of the German Society of Cardiology (DGK), the German Society of Respiratory Medicine (DGP) and the German Society of Pediatric Cardiology (DGPK) met for a Consensus Conference in Cologne, Germany. Aim of this Conference was to compile consensus based practice recommendations based on the 2015 European Pulmonary Hypertension guidelines, aiming at their practical implementation, considering country-specific issues, and including new evidence, where available. This article summarizes the results and updated recommendations 2018 of the working group on decompensated right heart failure (RHF), intensive care and perioperative management in patients with pulmonary hypertension. The RHF section comprises definition and pathophysiology, diagnosis and monitoring, identification of triggering factors and supportive therapy of RHF, volume management as well as PAH targeting therapy, therapy with inotropic, inodilator and vasopressor drugs, extracorporeal support and transplantation. The second part of this article summarizes preoperative management, perioperative monitoring and choice of anesthesia.